PENGARUH MANAJEMEN WAKTU TERHADAP PRODUKTIVITAS KERJA DI PT TELKOM WILAYAH TELEKOMUNIKASI JATIM SELATAN MALANG - Siti Nurbaya; Yosi Afandi; Tri Istining Wardani (Adbis: Jurnal Administrasi dan Bisnis, 2019)
The purpose of this study was to analyze the Effect of Time Management on Work Productivity in PT Telkom Regional Telecommunication in South Jatim Malang. This study uses observations, and questionnaires as data collection techniques and uses the Nonprobability Sampling method with certain sampling techniques (Purposive Samples). The number of samples in this study were 54 employees of the Customer Service and Human Resources (HR) Division. This research is a descriptive statistical research with tests carried out were the validity and reliability of the questionnaire distributed. The results of linear analysis show the Adjusted R Square value of 0.351, meaning that the percentage contribution of the influence of time management variables on work productivity is 35.1%. While the remaining 64.9% is influenced by other variables not discussed in this study.